Keeping up with the Bacillus cereus group: taxonomy through the genomics era and beyond. Issue 28 (3rd October 2022) - Carroll, Laura M.; Cheng, Rachel A.; Wiedmann, Martin; Kovac, Jasna
Abstract: The Bacillus cereus group, also known as B. cereus sensu lato ( s.l. ), is a species complex that contains numerous closely related lineages, which vary in their ability to cause illness in humans and animals. The classification of B. cereus s.l. isolates into species-level taxonomic units is thus essential for informing public health and food safety efforts. However, taxonomic classification of these organisms is challenging. Numerous—often conflicting—taxonomic changes to the group have been proposed over the past two decades, making it difficult to remain up to date. In this review, we discuss the major nomenclatural changes that have accumulated in the B. cereus s.l. taxonomic space prior to 2020, particularly in the genomic sequencing era, and outline the resulting problems. We discuss several contemporary taxonomic frameworks as applied to B. cereus s.l., including (i) phenotypic, (ii) genomic, and (iii) hybrid nomenclatural frameworks, and we discuss the advantages and disadvantages of each. We offer suggestions as to how readers can avoid B. cereus s.l. taxonomic ambiguities, regardless of the nomenclatural framework(s) they choose to employ. Finally, we discuss future directions and open problems in the B. cereus s.l. taxonomic realm, including those that cannot be solved by genomic approaches alone.